2010
DOI: 10.1517/14656560903551283
|View full text |Cite
|
Sign up to set email alerts
|

A review of erlotinib – an oral, selective epidermal growth factor receptor tyrosine kinase inhibitor

Abstract: This is a well-tolerated oral biologic agent with two approved clinical indications. More studies to individualize therapy and optimize dosing are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…10,11 EGFR activation may interfere with HCC response to sorafenib, [11][12][13] suggesting that EGFR inhibition may enhance tumor response. Erlotinib is an orally active inhibitor of EGFR tyrosine kinase 14,15 approved to treat patients with advanced nonsmall-cell lung and pancreatic cancers. 16 Moreover, in two single-arm, phase II trials, erlotinib showed modest antitumor activity but promising overall survival (OS) benefit in patients with unresectable HCC.…”
Section: 3mentioning
confidence: 99%
“…10,11 EGFR activation may interfere with HCC response to sorafenib, [11][12][13] suggesting that EGFR inhibition may enhance tumor response. Erlotinib is an orally active inhibitor of EGFR tyrosine kinase 14,15 approved to treat patients with advanced nonsmall-cell lung and pancreatic cancers. 16 Moreover, in two single-arm, phase II trials, erlotinib showed modest antitumor activity but promising overall survival (OS) benefit in patients with unresectable HCC.…”
Section: 3mentioning
confidence: 99%
“…In a large randomized phase III clinical trial, erlotinib showed superior to placebo for survival, progression-free survival, and tumor response rate Bareschino et al, 2007;Iyer and Bharthuar, 2010). Based on these positive results, US FDA granted erlotinib regular approval in 2004 for the treatment of advanced NSCLC patients after failure of a platinum-containing chemotherapy.…”
Section: Epidermal Growth Factor Receptor (Egfr) Inhibitorsmentioning
confidence: 99%
“…Based on these positive results, US FDA granted erlotinib regular approval in 2004 for the treatment of advanced NSCLC patients after failure of a platinum-containing chemotherapy. The maximum tolerated dose of erlotinib was 150 mg in a daily administration schedule and the most common adverse events were the rash and diarrhea Bareschino et al, 2007;Iyer and Bharthuar, 2010). Erlotinib received additional approval for the combination with gemcitabine chemotherapy for the treatment of advanced pancreatic cancer in 2005.…”
Section: Epidermal Growth Factor Receptor (Egfr) Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Erlotinib is administered to patients orally and the side effects are usually well tolerated (Li and Perez-Soler, 2009). Erlotinib has been approved by the FDA for treatment of recurrent non small cell lung cancer and for first-line treatment of advanced pancreatic cancer with gemcitabine (Iyer and Bharthuar, 2010). Given the importance of EGFR signaling to the HPV life cycle, we investigated whether erlotinib had activity against HPV-infected cervical cells.…”
Section: Introductionmentioning
confidence: 99%